(untitled) (Polis (Santiago), 2019)
This article examines the proposals of environmental governance of the eleven candidates for the city hall of São Paulo in 2016. The methodology consisted in the analysis of the content of the respective programs. The survey was conducted in the period from September to October 2016, during the election campaign. In addition, interviews were conducted with members of the candidates’ political marketing teams in order to qualitatively deepen the analysis. The conclusions show that out of the eleven candidates, nine presented environmental proposals in their government programs, with three different profiles: a comprehensive one, an intermediate one and a more limited one.